Steady state creep behaviour of NiAl hardened austenitic steel - Satyanarayana D.V.V.; Malakondaiah G.; Sarma D.S. (My University, 2025)
Creep behaviour of a Fe-Ni-Cr-Al alloy, hardened by ordered NiAl precipitates, has been studied over a temperature range 823-923 K at stresses ranging from 150 to 500 MPa. The behaviour following a stress dip or stress increment and the primary transient indicate that creep is recovery controlled. The stress dependence of steady state or minimum creep rate, covering almost five orders of magnitude, can be represented by a power-law with two distinct regimes of creep deformation. In the high stress regime, creep data reveal apparent stress exponents of 10-12 and an apparent activation energy of 282 kJ mol-1. On the other hand, the low stress regime is characterized by lower values of stress exponents (6-7) as well as activation energy (165 kJ mol-1). Creep data in the high stress regime is rationalized by invoking the concept of threshold stress. Activation energy for creep in both the regimes thus derived is equal to that for core or pipe diffusion of y-iron (159 kJ mol-1). The transition in stress exponents can be attributed to a change in dislocation by-pass mechanism from Orowan bowing in the high stress regime to general climb over the precipitates in the low stress regime. Creep data obtained on the alloy subjected to different ageing conditions provide indirect evidence for the suggested creep mechanisms. © 2002 Elsevier Science B.V. All rights reserved.